Complex Formation of the Tetracycline‐Binding Aptamer Investigated by Specific Cross‐Relaxation under DNP. Issue 15 (8th March 2019) - Aladin, Victoria; Vogel, Marc; Binder, Robert; Burghardt, Irene; Suess, Beatrix; Corzilius, Björn
Abstract: While dynamic nuclear polarization (DNP) under magic‐angle spinning (MAS) is generally a powerful method capable of greatly enhancing the sensitivity of solid‐state NMR spectroscopy, hyperpolarization also gives rise to peculiar spin dynamics. Here, we elucidate how specific cross‐relaxation enhancement by active motions under DNP (SCREAM‐DNP) can be utilized to selectively obtain MAS‐NMR spectra of an RNA aptamer in a tightly bound complex with a methyl‐bearing ligand (tetracycline) due to the effective CH3 ‐reorientation at an optimized sample temperature of approximately 160 K. SCREAM‐DNP can spectrally isolate the complex from non‐bound species in an RNA mixture. This selectivity allows for a competition assay between the aptamer and a mutant with compromised binding affinity. Variations in molecular structure and methyl dynamics, as observed by SCREAM‐DNP, between free tetracycline and RNA‐bound tetracycline are discussed. Abstract : Scream and shout : Selective solid‐state NMR spectra of an RNA aptamer in a bound complex are obtained using a novel method based on dynamic nuclear polarization (DNP). Specific cross‐relaxation enhancement by active motions under DNP (SCREAM‐DNP) allows the specific observation of the complex due to the presence of temperature‐activated methyl dynamics and can be used to study changes in both aptamer and ligand upon binding.